Recent advances in articular cartilage evaluation using computed tomography and magnetic resonance imaging. (27th February 2018) - Nelson, B. B.; Kawcak, C. E.; Barrett, M. F.; McIlwraith, C. W.; Grinstaff, M. W.; Goodrich, L. R.
Summary: Articular cartilage is a critical joint tissue and its evaluation remains a diagnostic challenge in horses. Coupled with a poor capacity for healing, early degenerative changes in articular cartilage are difficult to characterise using routine diagnostic imaging evaluations. Both computed tomography (CT) and magnetic resonance imaging (MRI) provide volumetric joint assessment and highlight morphological and quantitative properties of articular cartilage, improving assessment of this essential tissue. While the use of CT and MRI for joint evaluation is not new, there still remains a shortage of literature and scientific studies on the ability of these methods to evaluate articular cartilage in the horse. This review article summarises current CT and MRI techniques capable of characterising equine articular cartilage, highlights recent advances in these techniques and discusses the numerous methods studied in human subjects that have been minimally investigated in horses. Imaging techniques are presented in terms of their capabilities of offering morphological and quantitative evaluation along with a discussion of their benefits and limitations. Finally, it summarises the current state‐of‐the‐art approaches and identifies unmet clinical imaging needs to propel the advancement of articular cartilage and joint imaging in the horse.